(untitled) (Asian Journal of Applied Sciences, 2017)
In order to choose the right statistical test, when analyzing the data from an experiment, we must have at least a decent understanding of some basic statistical terms and concepts; some knowledge about few aspects related to the data we collected during the research/experiment (e.g. what types of data we have - samples, normal distribution with parameters, power of tests, how the data are organized, how many study groups (usually experimental and control at least) we have, are the samples paired or unpaired, and are the sample(s) extracted from a normally distributed/Gaussian population);a good understanding of the goal of our statistical analysis; we have to parse the entire statistical protocol in an well structured - decision tree /algorithmic manner, in order to avoid some mistakes.